Impact of cardiovascular risk factors on coronary heart disease and mortality among middle aged diabetic men: a general population study. - Rosengren, A. (1989)
OBJECTIVE--To investigate the effect of cardiovascular risk factors on coronary heart disease and all cause mortality in middle aged diabetic men. DESIGN--Prospective population study based on data collected from second screening (from 1974 to 1977) in the multifactor primary prevention trial and follow up until March 1983. SETTING--Gothenburg, Sweden. SUBJECTS--6897 Men aged 51 to 59, of whom 232 were self reported diabetics and 6665 were non-diabetic; none had a history of myocardial infarction. MAIN OUTCOME MEASURES--Incidences of coronary heart disease and mortality from all causes. RESULTS--Diabetic men with a serum cholesterol concentration greater than 7.3 mmol/l had a significantly higher incidence of coronary heart disease during follow up than those with a concentration less than or equal to 5.5 mmol/l (28.3% v 5.4%; p = 0.020); corresponding figures for non-diabetic men were 9.4% and 2.4% respectively. In multivariate logistic regression analyses serum cholesterol concentration and smoking habit were independent predictors of coronary heart disease (odds ratio serum cholesterol concentration 6.1 (95% confidence interval 2.1 to 17.6) current smoking 2.9 (1.1 to 7.5)) and of all cause mortality (3.2 (1.3 to 7.9), 3.0 (1.4 to 6.7) respectively) in diabetic men whereas systolic blood pressure, body mass index, family history, marital state, and alcohol abuse were not. Low occupational class was an independent predictor of mortality (2.4 (1.01 to 5.5)), but not of coronary heart disease, in diabetic men. CONCLUSIONS--Middle aged diabetic men with hypercholesterolaemia are at very high risk of developing coronary heart disease and of dying prematurely. Lowering serum cholesterol concentration in such subjects seems to be warranted.